GENERATION AND COLLECTION PRACTICES OF ORGANIC KITCHEN WASTE IN HOUSEHOLDS OF MANIPAL - Lalitha Simon; Shivali Patel; Anysha Mattu; Teresa Chirayil (European Scientific Journal, ESJ, 2013)
The present study was conducted to understand the organic kitchen waste management practices in households of Manipal. The general steps in waste management are 1. Generation 2. Collection 3. Sorting 4. Separation 5. Transfer 6. Transport and 7. Disposal. This study was aimed at understanding the management practices at the first two steps only ie. Generation and Collection. Data was collected by interviewing the household members, with the help of a structured questionnaire. The study brought out the various types of wastes generated, the constituents and their quantum in organic kitchen wastes as well as the activities which happen at the generation and at the two waste collection points.